Decoding the Methylome: Insights into the Epigenetic Regulation of Polycystic Ovarian Syndrome through Mitochondrial DNA Methylation - Kolasseri, Aparna Eledath; Tamizhselvi, Ramasamy; Jayanthi, Sivaraman (Current Genomics, 2025)
Polycystic Ovarian Syndrome (PCOS) imposes significant societal health and economic challenges. The precise determinants behind the global prevalence of PCOS are still poorly understood. However, epigenetic modifications in PCOS, such as DNA methylation, have been recognized as a method by which the environment interacts with the genome. Evidence suggests that changes in mitochondrial (mt)DNA methylation may have a role in the heightened occurrence of PCOS. This article provides a comprehensive overview of nuclear DNA methylation, mitochondrial DNA methylation, and their significance in regulating gene expression. Pre-existing scholarly works shed insight into the complex interaction of DNA methylation and other epigenetic modifications associated with PCOS. In addition, this review gathers a detailed explanation of several methodologies employed to assess alterations in DNA methylation at specific sites and across the nuclear and mitochondrial genomes. Integrating mtDNA methylation alterations may be a promising diagnostic strategy for PCOS, potentially paving the way for novel therapeutic interventions.
Keywords: bisulfite sequencing